2011
DOI: 10.1111/j.1365-246x.2011.05275.x
|View full text |Cite
|
Sign up to set email alerts
|

Local stretch zeroing NMO correction

Abstract: S U M M A R YIn this paper we present a new method of normal move-out (NMO) correction called local stretch zeroing (LSZ) method that avoids NMO stretch. The method eliminates the theoretical curves that generate interpolated data samples responsible for NMO stretch. Pre-correction time sampling interval is preserved by reassigning and zero padding of true data samples. The optimum mute zone selection feature of the LSZ method eliminates all interfering reflection events at far offsets. The resulted stacked se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This erratum corrects an error in a figure of Kazemi & Siahkoohi (2012). The image shown as panel (a) of fig.…”
mentioning
confidence: 67%
“…This erratum corrects an error in a figure of Kazemi & Siahkoohi (2012). The image shown as panel (a) of fig.…”
mentioning
confidence: 67%
“…Zhang et al (2015) showed how such corrections can improve subsequent prestack inversion to map geomechanical properties in an unconventional Fort Worth Basin, Texas, shale play. Kazemi and Siahkoohi (2012) propose an alternative method to minimize migration stretch. To avoid stretching the nonzero offset traces, the moveout correction needs to be constant for all samples that form part of a reflection event.…”
Section: Nonstretch Normal Moveout (Matching-pursuit Normal Moveout) mentioning
confidence: 99%
“…Many papers have presented effective methods to alleviate the NMO stretch (Dunkin and Levin ; Rupert and Chun ; Barnes ; Alkhalifah ; Dong ; Shatilo and Aminzadeh ; Brouwer ; Hilterman and Van Schuyver ; Lazaratos and Finn ; Hassan, Penny and Satish ; Kazemi and Siahkoohi ; Zhang et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Given migration stretch, the distortion is a consequence of the varying incident angle (Tygel et al 1994;Roy et al 2005). * E-mail: qiancheng.liu@kaust.edu.sa Many papers have presented effective methods to alleviate the NMO stretch (Dunkin and Levin 1973;Rupert and Chun 1975;Barnes 1992;Alkhalifah 1997;Dong 1999;Shatilo and Aminzadeh 2000;Brouwer 2002;Hilterman and Van Schuyver 2003;Lazaratos and Finn 2004;Hassan, Penny and Satish 2010;Kazemi and Siahkoohi 2012;). However, conventional NMO methods cannot image complex subsurface structures well, and thus prestack migration stands out (Yilmaz 2001).…”
Section: Introductionmentioning
confidence: 99%